2018
DOI: 10.14254/1800-5845/2018.14-2.11
|View full text |Cite
|
Sign up to set email alerts
|

Network Topology of Renewable Energy Sector in Stock Exchange

Abstract: In today's global economy, the most prominent position clean energy is basically viewed as the highest-speed growing branch. Sustainable energy, perpetual climate change, and technological advancements are the reasons from which this foreground position results from. Regarding the debate of effects of pollution and the importance of the alternative fuels, the more awareness people improve, the more interested they are to invest in clean energy. This paper brings to a focus the inspection of clean energy and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(17 reference statements)
0
2
0
1
Order By: Relevance
“…Scientists [67][68][69][70][71][72][73][74][75][76] have confirmed that macroeconomic indicators influence a country's energy security and energy efficiency. Simultaneously, human capital and financial development have influenced CO 2 emissions and energy efficiency [67,68,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. Malinauskaite et al [87] confirmed that energy efficiency of the industry sector has influenced the achievement of the goals of the Green Deal Policy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scientists [67][68][69][70][71][72][73][74][75][76] have confirmed that macroeconomic indicators influence a country's energy security and energy efficiency. Simultaneously, human capital and financial development have influenced CO 2 emissions and energy efficiency [67,68,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. Malinauskaite et al [87] confirmed that energy efficiency of the industry sector has influenced the achievement of the goals of the Green Deal Policy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…В этой связи интерес представляют другие факторы, способствующие переходу электроэнергетики на возобновляемые источники энергии, которые могут быть использованы для развития механизмов регулирования. Например, в работе (Kazemilar et al, 2018) исследуются взаимосвязи показателей фондового рынка и развития альтернативной энергетики.…”
Section: рисунокunclassified
“…There is a gap between potential and actual energy generation from renewable energy sources [22,23] and indicators of its productivity [24,25]. A possible solution, Energies 2021, 14, 4490 2 of 19 in this case, will be to expand the use of green innovations, smart grids [26,27], promising energy storage technologies [28,29]. The accelerated consumption of renewable energy resources is stimulated in the interested communities [30].…”
Section: Introductionmentioning
confidence: 99%